Dual Antiplatelet Therapy Regimens and Duration for Intracranial Stenting Procedures: Literature Review - Paliulytė, Milda; Šustickas Gytis (Lietuvos chirurgija, 2023)
Objectives of the study. Our aim was to analyse different antithrombotic drug regimens and duration in intracranial stenting procedures (stent assisted coiling, flow diverter) for unruptured aneurysms and based on the literature review from 2017–2023 to implement dual antiplatelet therapy algorithm for neuro-interventional procedures in Lithuania. Research methods and methodology. A comprehensive literature search of PubMed, BioMed Central, BMJ Journals, EBSCO Publishing, SAGE Journals Online, ScienceDirect, SpringerLink was conducted by two independent readers (MP, GŠ) for studies published from January 2017 to April 2023. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. 23 studies: 6 retrospective cohort, 11 retrospective case-control, 1 prospective cohort, 1 prospective randomized-control, 1 systemic literature review, 3 metanalysis observational studies were identified. Results and conclusions. We found widespread variation in practices even among the same country centres, lending credence to the importance of a future prospective studies of dual antiplatelet drug therapy (DAPT) regimens and duration for the purpose of deriving optimal methods and streamlining tactics. Our suggested algorithm for DAPT in neuro-interventional procedures in Lithuania is provided in Graph 1.